Semiclassical dynamics of quasiparticles in the nonlocal Fisher-KPP model - Shapovalov, Alexander V. (Моделирование нелинейных процессов и систем : седьмая международная научная конференция : материалы конференции)
We construct asymptotic solutions to the nonlocal Fisher-KPP equation using the formalism of the semiclassical approximation based on the Maslov complex germ method. The attractive feature of the solutions in this work is that their behave as quasiparticles whose dynamics stems from the original FKPP equation.